Dick Sand: A Captain at Fifteen - Verne, Jules, 1828-1905 (Salt Lake City, UT : Project Gutenberg, 2004)
"Dick Sand: A Captain at Fifteen" by Jules Verne is a novel published in 1878. When a whaling expedition goes tragically wrong, fifteen-year-old Dick Sand finds himself commanding a ship with no experienced crew. Through treachery and sabotage, the vessel is secretly diverted to Africa instead of South America, delivering its passengers into the hands of slave traders. Dick must protect Mrs. Weldon and her young son while navigating the brutal realities of the African slave trade in this adventure tale addressing one of history's darkest practices. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Dick_Sand,_A_Captain_at_Fifteen
Release date is 2004-04-01
Produced by Norm Wolcott and PG Distributed Proofreaders
Keywords: Ship captains -- Fiction; Adventure stories; Sailors -- Fiction; Voyages and travels -- Fiction; Enslaved persons -- Fiction; Whales -- Fiction; Cooks -- Fiction